What Jovellanos thought about novels Lo que Jovellanos pensaba de las novelas - Joaquín ÁLVAREZ BARRIENTOS (Cuadernos Dieciochistas)
This work studies the ideas of Jovellanos on the novel of his time. Uses for it the censures that he wrote between 1782 and 1789, plus a letter of beginnings of the ninety on the Quijote de la Cantabria. The analysis settles down from the criteria of utility, entertainment and education, necessary to have patriotic citizens. Este trabajo estudia las ideas de Jovellanos sobre la novela de la época. Para ello se utilizan las censuras que escribió entre 1782 y 1789, más una carta de comienzos de los noventa sobre el Quijote de la Cantabria. El análisis se establece desde los criterios de utilidad, entretenimiento y educación, necesarios para tener ciudadanos patriotas.